Adubação NPK em três sistemas de associação de milho com feijão (Phaseolus vulgaris L.) - A Antunes de Oliveira, Luiz; Domingos Galvão, José; A Nogueira Fontes, Luiz; Reis Condé, Alcides (Revista Ceres, 2025)
Two field experiments of different planting dates were conducted during the rainy season in 1980/81 at Viçosa, Minas Gerais, with the objective to obtain information about NPK fertilization for association systems of maize and beans.